Protein restriction in CKD: an outdated strategy in the modern era - Abdullah Bawazir; Joel M Topf; Swapnil Hiremath (Brazilian Journal of Nephrology)
Abstract Chronic kidney disease (CKD) management has traditionally emphasized dietary protein restriction to slow disease progression and delay end-stage renal disease (ESRD). However, evidence from trials questions the supposed efficacy of this approach and also highlights potential risks such as malnutrition and reduced quality of life. This review discusses the rational for protein restriction in CKD, critiques the existing evidence, and advocates for personalized care that focuses on nutritional adequacy and effective pharmacotherapy. Important advances in CKD treatment, including ACE inhibitors, SGLT2 inhibitors, and GLP-1 receptor agonists, are discussed to propose a comprehensive strategy that optimizes patient outcomes.